Morphological, anatomical, and preliminary phytochemical characterization of Olax psittacorum (Willd.) Vahl. A Wild leafy Vegetable - Jayendra G, Nakade; Praveenkumar N. Nasare (The Bioscan, 2025)
Olax psittacorum (willd.) Vahl.is a perennial shrubby climber, distributed all over the tropical and subtropical region. This study focused on the morphological, anatomical, and phytochemical characteristics of Olax psittacorum. The findings revealed that the plant typically grows to a height of 120 to 200 mostly erect and climbing in nature with white flowers having axillary inflorescence. Leaves showed a well-developed epidermis with unicellular trichomes. Mesophyll tissue is filled with oils & globules, crystals of calcium oxalate& chlorenchymatous tissue. Stem and root consist of open and bicollateral endarch vascular bundle. Phytochemical analysis of leaves crude powder extract shows the presence of carbohydrates, proteins. fats, alkaloids, flavonoids, tannins & resin were present. The result indicates that the leaves are rich in primary and secondary metabolites, Therefore, it is recommended as a plant for its wide use as a wild leafy vegetable and phytopharmaceutical important.